RANCANG BANGUN SISTEM PEMBAYARAN SPP BERBASIS WEB DENGAN METODE WATERFALL ( STUDI KASUS : SMP ISLAM RAUDLATUL HIKMAH ) - Subkhi, Alfan; Omar Arrizal Javani; Miftahul Ulum; Perani Rosyani (Buletin Ilmiah Ilmu Komputer dan Multimedia, 2024)
The tuition payment system is an important part of school administration that requires efficiency and reliability. This research aims to design and implement a web-based tuition payment system using the Waterfall method, with a focus on Raudlatul Hikmah Islamic Middle School as a case study. The Waterfall method was chosen because of its suitability for system development with structured steps, starting from requirements analysis to final testing. This research begins with a needs analysis stage, where the basic needs of a tuition payment system are identified. Then, system design is carried out by designing an intuitive and functional user interface. Implementation was carried out by coding and testing the system, as well as integrating it with the existing infrastructure at Raudlatul Hikmah Islamic Middle School. The research results show that the developed web-based tuition payment system has succeeded in increasing efficiency in the school administration process, reducing manual errors, and increasing information transparency for parents. The conclusion of this research confirms that the Waterfall method can be an effective approach in developing school information systems such as tuition payment systems. It is hoped that this research can serve as a guide for other schools that wish to increase their administrative efficiency through the application of information technology.